ICS Educational Module: Cough stress test in the evaluation of female urinary incontinence: Introducing the ICS-Uniform Cough Stress Test - (:unkn) unknown (WILEY, 2018)
IntroductionA cough stress test (CST) is recommended in the evaluation of the uncomplicated female patient with the complaint of stress urinary incontinence (SUI) to identify the sign of SUI, and is often used as an outcome measure following SUI treatment. However, there has been no standardization of the performance or reporting of CST. A working group of the International Continence Society (ICS) has developed an educational module, comprising a Powerpoint presentation and evidence base manuscript, to instruct on the performance, interpretation, and reporting of the CST in a standardized manner: the ICS-Uniform Cough Stress Test (ICS-UCST). MethodsThe working group performed a PUBMED literature search of articles (observational/experimental and reviews) published prior to 2017 that mentioned a CST. The evidence base examined various variables in performing a CST as well as sensitivity/specificity and positive/negative predictive values of CST. ResultsThe variables involved in performing/interpreting an ICS-UCST include: patient positioning, degree of bladder filling, number, and forcefulness of coughs, and method of SUI detection. For the ICS-UCST it is recommended that the patient be in a supine/lithotomy position with 200-400mL of fluid in the bladder. She coughs forcefully 1-4 times and the examiner directly visualizes the urethral meatus for the presence of leakage. Leakage of fluid from the urethral meatus coincident with/simultaneous to the cough(s) is considered a positive test. ConclusionThis module provides instructions to educate a uniform CST (the ICS-UCST), with the aim of improving the clinical practice of cough stress testing in female patients with urinary incontinence.
Keywords: cough stress test; stress urinary incontinence; LEAK-POINT PRESSURE; URODYNAMIC EVALUATION; CLINICAL-PRACTICE; OUTCOME MEASURES; PAD TEST; WOMEN; DIAGNOSIS; CYSTOMETRY; VALSALVA; DYSFUNCTION